Pendidikan Islam Moderat dalam Perspektif Hasan Al-Banna - Fauzi, Ibnu Abdillah Hammam; Thoyyar, Husni (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2017)
This article is a qualitative study using analytical methods and approach to the study of literature. Hasan al-Banna (1906-1949) is a Muslim reformer who Introduced the da’wah movement with educational methods, so that the movement known as the movement tarbiyah. Typical education in his movements redirect the output to be moderate in religious behavior. Islamic moderate education by Hasan Al Banna idea is universal education, non-dichotomous namely comprehensive, conceptually and practically